2020
DOI: 10.1016/j.artd.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Early failure of a modern moderately cross-linked polyethylene acetabular liner

Abstract: Modern polyethylene components for total hip arthroplasty have shown excellent long-term wear properties. However, among 204 primary total hip arthroplasty procedures performed by one surgeon using the Exactech Connexion GXL Liner, we identified 5 cases of severe polyethylene wear and osteolysis which occurred within 5 years of the index surgery. Among the 5 cases, all patients had a size 36 head with an acetabular component from size 52 to 56 mm. All patients had a UCLA activity scale score of at least 6 at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…the "polar-locking" mechanism that is combined with antirotational tabs. Kahlenberg et al [50] identified five cases (among 204 primary THA) of severe polyethylene wear (0.265 mm/year rate) and osteolysis which occurred within 5 years of the index surgery using this specific PE. Ceramic heads with 36-mm diameter were used in all the cases.…”
Section: Crosslinked Polyethylene Failuresmentioning
confidence: 99%
“…the "polar-locking" mechanism that is combined with antirotational tabs. Kahlenberg et al [50] identified five cases (among 204 primary THA) of severe polyethylene wear (0.265 mm/year rate) and osteolysis which occurred within 5 years of the index surgery using this specific PE. Ceramic heads with 36-mm diameter were used in all the cases.…”
Section: Crosslinked Polyethylene Failuresmentioning
confidence: 99%
“…Charnley used Poly Tetra Fluro Ethylene (PTFE) material due to its inertness, high thermal stability, and hydrophobic properties but observed higher wear rate, which was referred by McKee 4 . Attempts were made in using Polyethylene (PE), 5 cross‐linked polyethylene (XLPE), 6 Ultra‐High Molecular Weight Polyethylene (UHMWPE), 7 and High‐Density Polyethylene (HDPE) 8 with ceramic particles as liner material in order to counter the drawbacks encountered in PTFE liner 9,10 . Biocomposites were also used to resolve the problems of wear in polyethylene liners 11 …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a more recent randomized controlled trial with 10-year follow-up demonstrated that cross-linked polyethylene liners have significantly reduced wear and revision rates compared to conventional polyethylene [ 7 ]. Despite these potential benefits, there have been a few reports of early failures of cross-linked polyethylene acetabular liners, potentially due to differences in mechanical properties compared to conventional liners [ [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%